THE IMPACT OF DISPROPORTIONATE DEVELOPMENT OF COUNTRIES ON THEIR READYNESS FOR TRANSFORMATIONS WITHIN THE IMPLEMENTATION OF THE SUSTAINABLE DEVELOPMENT CONCEPT: А HYPOTHETICAL APPROACH - Korolchuk , L. V. (The actual problems of regional economy development, 2021)
The article raises the issue of the world's readiness for transformations, which involves the implementation of the generally accepted concept of sustainable development, based on complex modified socio-economic processes: the transition to green, low-carbon, circular economy based on eco-innovation and decoupling, which minimizes dependence on economic costs of non-renewable natural resources. It is hypothesized that sustainable development is more involved in developed countries with a high standard of living, leaders in globalization, as their production has long been not placed within national borders and that is why their capital migrated to other countries in search of cheaper factors of production, maximizing economic benefits and expanding their political influence. The primary needs of the population of developed countries are more satisfied, and therefore the needs of the highest level dominate, cultivate universal values ​​and public good, which motivates them to actively develop the processes of economic greening, taking care of our planet fate as a legacy for future generations. The aim of the study is to identify the correlation between the standard of living of the countries and the degree of their involvement in the implementation of the sustainable development concept. To confirm the hypothesis, based on the method of calculating the correlation coefficient of Fechner, the correlation between the standard of living of the country and the degree of its involvement in sustainable development on the basis of ratings on GDP at purchasing power parity per capita as an indicator of living standards and global indices that reflect and characterize the economic, environmental, innovation and social components of such processes. The results of the study showed a direct noticeable relationship between living standards and the degree of involvement in sustainable development for the most developed countries, as well as a direct relationship with very high density for the least developed countries, which serves as a reason for further deeper study of this problem to ensure the successful implementation of the concept of sustainable development in the world and at the level of nation states.